KH. Zainal Musthafa’s Struggle in Developing the Nation's Intellectual Life - Tatang Hidayat; Aam Abdussalam (Ulumuna, 2019)
Many national independent struggle movements in Indonesia began from traditional Islamic boarding schools (pondok pesantren). One of the the movements was established by KH. Zainal Musthafa of Tasikmalaya, West Java. This study aims to examine this scholar’s struggle of independence and his spirit in developing the nation's intellectual life. Based on interview and historical archives, this study shows that KH. Zainal Musthafa plays a vital role in the independence struggle. He was a role model, who was not only a Muslim religious scholar (‘ulamā’), but also a fighter against colonialism. His struggle was motivated by the values and principle of tawḥīd (Oneness of God) and the spirit of Indonesian independence. His struggle furthermore departed from and was shaped by, the teachings offered at traditional Islamic boarding school. This suggests that traditional Islamic educational system, spiritualism and mode of Islamic religiosity developed by pesantren constitute one of the most relevant aspects of Islam in the struggle for Independence and, as this paper argues, remain relevant to the contemporary Indonesian spiritual and intellectual life. It is through pesantren and their leaders that Islamic spiritualism and public intellectualism have thrived up to the present.